Exploring the self-efficacy and self-care-based stroke care model for risk factor modification in mild-to-moderate stroke patients - Rasyid, Al; Pemila, Uke; Aisah, Siti; Harris, Salim; Wiyarta, Elvan; Fisher, Marc (Frontiers in Neurology, 2023)
Context: The worldwide burden of stroke is projected to grow unless proper stroke education is implemented. Information alone cannot promote patient self-efficacy and self-care and reduce risk factors. Aim: This trial aims to test Self-efficacy and self-care-based Stroke Education (SSE) on changes in self-efficacy, self-care, and risk factor modification. Design, setting, participant: Single-center, double-blinded, interventional, 2-arm randomized controlled trial with a 1- and 3-month follow-up in Indonesia. Between January 2022 and October 2022, 120 patients were prospectively enrolled from Cipto Mangunkusumo National Hospital, Indonesia. Participants were assigned using a computer-generated random number list. Intervention: SSE given before discharge from the hospital. Primary outcome measure: Self-care, self-efficacy, and stroke risk score one month and three months after discharge. Secondary outcome measure: Modified Rankin Scale, Barthel Index, and blood viscosity at one month and three months after discharge. Results: 120 patients (intervention n=60; standard care n=60) were randomized. In the first month, the intervention group showed a more significant change in self-care (4.56 [95% CI: 0.57, 8.56}), self-efficacy (4.95 [95% CI: 0.84, 9.06]), and stroke risk (-2.33 [95%CI: -3.19, -1.47]) compared to the controlled group. In the third month, the intervention group also showed a more significant change in self-care (19.28 [95% CI: 16.01, 22.56]), self-efficacy (19.95 [95% CI: 16.61, 23.28]), and stroke risk (-3.83 [95%CI: -4.65, -3.01]) compared to the controlled group. Conclusion: SSE may boost self-care and self-efficacy, adjust risk factors, enhance functional outcomes, and decrease blood viscosity. Trial Registration: ISRCTN11495822.